Chloricalla Kerremans, 1893 not Chloricala Bellamy, 1985 (Coleoptera: Buprestidae: Agrilinae) - Ponting, John (Zootaxa, 2018)
In 1893, Kerremans described a new genus of buprestid beetle, naming it Chloricalla. He subsequently used the same spelling of that name on at least two occasions (Kerremans 1900 & Kerremans, 1903).